The Urgency of ICT in Elementary Education - Yudi Kurniawan; Riski Muliyani; Lili Yanti; Iip Istirahayu; Dian Mayasari; Emi Sulistri; Mardian Mardian; Eti Sunarsih (International Journal of Public Devotion, 2018)
This activity was a socialization and training to citizen in order to apply computer into learning process in the elementary schools. This activity aims to provide knowledge and skills for the use of ICT especially computer and internet and foster interest and motivation of students to learn. The target in this task were all of students of SDN 62 in East Singkawang Sub-District. The methods used in PPM activities are briefing and simulation. The advantage of this activity could be obtained by participation of students in this social activities was provided the knowledge and skills on implementation of ICT as a tool of learning so that elementary school students more skilled in their class. These training activities can also contribute to the advancement and development of technology